2022
DOI: 10.1177/03000605221129154
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of carbapenem-resistant Enterobacteriaceae (CRE) strains in patients with COVID-19 in the ICU ward: a retrospective case–control study

Abstract: Objective To identify carbapenem-resistant Enterobacteriaceae (CRE) in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; COVID-19) and to determine whether they had different risk factors for the acquisition of CRE than patients without COVID-19. Methods This retrospective single-centre, case–control study enrolled patients with and without COVID-19. The demographic, clinical, infection, colonization and mortality data were compared between the two groups. Results A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Longer lengths of ICU stay, carbapenem treatment, corticosteroid treatment, and invasive mechanical ventilation were frequently applied to COVID-19 ICU patients, increasing their susceptibility to CRE acquisition [17]. Additionally, elderly patients admitted to the COVID ICU were likely to be initially undetectable CRE carriers from long-term care facilities in the Korean medical environment [18]. Infection prevention management in the COVID ICU was also challenging due to the wearing of protective clothing and the risk of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer lengths of ICU stay, carbapenem treatment, corticosteroid treatment, and invasive mechanical ventilation were frequently applied to COVID-19 ICU patients, increasing their susceptibility to CRE acquisition [17]. Additionally, elderly patients admitted to the COVID ICU were likely to be initially undetectable CRE carriers from long-term care facilities in the Korean medical environment [18]. Infection prevention management in the COVID ICU was also challenging due to the wearing of protective clothing and the risk of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics exert their effects by producing short-chain fatty acids from metabolic precursors, leading to similar downstream effects, such as immune modulation and increased mucosal barrier function [18]. Moreover, they may have the added effect of producing their own antimicrobial compounds, physically occupying the epithelial niche, and limiting the ability of other pathogens to colonize the enteric microbiome; specifically, their main effect on the clearance or decolonization of MDRO is dysbiosis [7], which possesses the primary mechanism of CRE acquisition and expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Thomas et al reported an emerging in carbapenemase-resistant Enterobacteriaceae isolates by 42.8% in Brazil, and an increase from 73.6% to 88.4% in the total number of carbapenemase genes detected. The emergence of new genes that have not been identified yet has been reported in Chile, Dominica and Belize, while Peru, Ecuador, Venezuela and Costa Rica have reported the emergence of new combinations of carbapenemase [53][54][55][56][57][58].…”
Section: Impact Of the Covid-19 Pandemic On Bacterial Resistancementioning
confidence: 99%